2006
DOI: 10.1002/jor.20135
|View full text |Cite
|
Sign up to set email alerts
|

Minced cartilage without cell culture serves as an effective intraoperative cell source for cartilage repair

Abstract: Traumatic articular cartilage injuries heal poorly and may predispose patients to the early onset of osteoarthritis. One current treatment relies on surgical delivery of autologous chondrocytes that are prepared, prior to implantation, through ex vivo cell expansion of cartilage biopsy cells. The requirement for cell expansion, however, is both complex and expensive and has proven to be a major hurdle in achieving a widespread adoption of the treatment. This study presents evidence that autologous chondrocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
196
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(206 citation statements)
references
References 28 publications
5
196
1
4
Order By: Relevance
“…Therefore, the promising outcome achieved in this study indicates that morselising the cartilage in approximately 1-mm 3 pieces might provide ideal movement of chondrocytes around cartilage fragments and subsequent multiplication and matrix production in the loading regime. This is consistent with previous studies, which report an inverse relationship exists between cartilage fragment size and amount of cartilage-like tissue outgrowth (smaller size, more chondral growth) [3,6]. Moreover, immunohistochemistry visualised that neocartilaginous tissue outgrown from the surrounding minced fragments was stained with stronger collagen type I and weaker collagen type II and aggrecan, which illustrated that the newly formed tissue within the setting described here was immature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the promising outcome achieved in this study indicates that morselising the cartilage in approximately 1-mm 3 pieces might provide ideal movement of chondrocytes around cartilage fragments and subsequent multiplication and matrix production in the loading regime. This is consistent with previous studies, which report an inverse relationship exists between cartilage fragment size and amount of cartilage-like tissue outgrowth (smaller size, more chondral growth) [3,6]. Moreover, immunohistochemistry visualised that neocartilaginous tissue outgrown from the surrounding minced fragments was stained with stronger collagen type I and weaker collagen type II and aggrecan, which illustrated that the newly formed tissue within the setting described here was immature.…”
Section: Discussionsupporting
confidence: 92%
“…Fullthickness articular cartilage was dissected aseptically from fetlock joints of three, three to four month-old calves directly after slaughter. Cartilage tissue was minced into small fragments (∼1 mm 3 ) with a surgical scalpel in the presence of Tyrode's balanced Salt Solution (TBSS). Isolated fragments of MC were suspended in fibrinogen solution (75 μl) and mixed with thrombin solution (100 μl) immediately prior to being transferred into the PU ring at about 80 mg cartilage fragments per ring.…”
Section: Harvest and 3d Culture Systemmentioning
confidence: 99%
“…Because CaRes1 already adopts an approach that does not include a monolayer proliferation step, it suggests sufficient cell numbers may already be available. Attempts to eliminate cell culture have been made using minced cartilage intraoperatively as a cell source, which led to enhanced repair [59]. Although this method used cartilage, and therefore chondrocytes, as a cell source, it is likely future single-surgery treatments will use stem cells that can be isolated during the operation and manipulated within the operating room before immediate implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The technique involves a single-stage procedure where cartilage is harvested from a non-weight-bearing portion of the knee, is minced, and then seeded onto a resorbable copolymer foam with fibrin glue which is implanted with polydioxanone (PDS) staples [22]. Equine data from Frisbie et al set the stage for CAIS as they demonstrated similar outcomes to a modified ACI procedure with regard to type II collagen and proteoglycan content [23].…”
Section: Minced Cartilage Productsmentioning
confidence: 99%